IMPLEMENTASI MAXIMUM POWER POINT TRACKING DENGAN METODE INCREMENTAL CONDUCTANCE DAN HILL CLIMBING UNTUK PENGISIAN BATERAI DARI SISTEM PHOTOVOLTAIC - Nadia Kusuma Putri; Rini Nur Hasanah; Moch. Dhofir (Jurnal Mahasiswa TEUB, 2023)
Renewable energy is an alternative energy as a substitute for fossil fuels, one of which is solar energy. The problems with photovoltaic technology are low energy conversion efficiency and inconsistent solar radiation. So that from these problems it is necessary to optimize the output power of solar panels using Maximum Power Point Tracking (MPPT) which works by tracking the maximum power point that can be generated by the solar panel system and keeping it always working at that point. In this study, this MPPT Solar Charge Controller uses a Buck-Boost Converter, as well as Incremental Conductance and Hill Climbing as control methods. Both of these methods will be analyzed by comparing the increase in output power through MATLAB Simulink software simulation. Based on the results obtained from the simulations and calculations using the two MPPT methods, it was found that there was an increase in the output power of the solar panel system by 31.17W or 56.9% for the Incremental Conductance method and 7.23W or 13.2% for the Hill Climbing method, compared to PV systems without using MPPT. Index Terms--Photovoltaic System, Power Optimization, MPPT, Incremental Conductance, Hill Climbing, Buck-Boost Converter